Meta‐analysis of age‐related cognitive decline reveals a novel locus for the attention domain and implicates a COVID‐19 related gene for global cognitive function. (20th December 2022) - Acharya, Vibha; Fan, Kang‐Hsien; Snitz, Beth E; Ganguli, Mary; DeKosky, Steve; Lopez, Oscar L.; Feingold, Eleanor; Kamboh, M. Ilyas
Abstract: Background: Cognition is a highly complex polygenic trait. A limited number of studies have explored the genetic basis of cognitive decline in aging populations using cognitive domain specific measures. Method: To identify genetic markers for cognitive decline, we conducted a genome‐wide association meta‐analysis and gene‐based tests on five different cognitive domains (attention, language, executive function, visuospatial abilities, memory) and global cognition on 3, 068 older individuals (≥65 years) of European ancestry derived from three prospective cohorts: Gingko Evaluation Memory Study (GEMS), Monongahela‐Youghiogheny Healthy Aging Team (MYHAT) and Monongahela Valley Independent Elders Survey (MoVIES). All subjects completed a comprehensive neuropsychological battery of tests covering the examined domains. A linear mixed effects model was used to estimate the longitudinal decline in cognitive scores after adjusting for sex, baseline age and education. Global cognitive decline was defined as a decline in average performance in neuropsychological tests across the five domains. Result: Genome‐wide significant association of APOE*4 was observed with decline in the memory domain (p= 8.93E‐09) and global cognitive function (p= 2.69E‐08).We identified a novel locus for decline in the attention domain on chromosome 9 in an intergenic region between RASEF / FRMD3 (p = 3.17E‐08). Gene‐based analysis identified TMPRSS11D as the top gene for decline in global cognition (Bonferroni corrected p= 2.48E‐06). TMPRSS11D plays a role in host‐defense system and recent studies have shown that it activates spike protein of SARS‐CoV‐2 and facilitates viral entry to cell ( Viruses 2021;13:384; J Biol Chem 2021; 296:100135). Conclusion: We have identified a novel locus for longitudinal decline in the attention domain, replicated the association of APOE*4 with the global and memory domains, and potentially implicated the role of TMPRS11D in cognitive decline through gene‐based analysis. The association of TMPRSS11D with cognitive decline might help to explain cognitive impairment observed in some patients after COVID‐19 infection ( Br J Anaesth 2021; 25:e54; JAMA Netw Open 2021; 4(10):e2130645 ). While functional studies might help to understand the underlying molecular mechanism of the associated loci, cognitive decline studies with larger samples are essential to establish these findings.